An Examination of Management Committees' Attitudes toward Teacher Motivation in Community Colleges - Mainali, Hari Lal (Chaturbhujeshwar Academic Journal, 2023)
A positive attitude from an employer raises employee morale, lowers stress levels, and creates a more motivating work environment. Therefore, it is essential for organizational development and employee motivation. The objective of this study is to evaluate the attitudes of CMC members toward teacher motivation in community colleges. As a research methodology, a qualitative case study design was used. The population consisted of three participants who were purposively selected from three different community colleges. The participants were interviewed in-depth to assess their perspectives on teacher motivation. The gathered data were transcribed, examined ethically, and divided into three significant themes. The study found that CMC has favorable views regarding merit-based responsibility, employee promotion by TU regulations, and teacher appreciation and recognition. However, the CMC has poor attitudes towards teachers who actively participate in politics, the irregular in the classroom, and have poor academic performance. In light of these findings, the study failed to identify that CMC is hardly responsible in some major teachers’ motivational cases. Accordingly, it is suggested that CMC should take full responsibility for teachers’ motivation in college for optimal performance. And teachers should also prioritize their professional duties above other responsibilities. Consequently, the contribution of the study will be valuable to stakeholders in community colleges for the policy-making process in the future.